The Problem of Globalization in the Arkounian Thought - Altawallbeh, Mohammad (Jordan Journal of Social Sciences, 2019)
It has become evident that issues of renewed consciousness, related to globalization, are connected to some troubling questions concerning Arab-Islamic Identity which is imposed voluntarily or involuntarily on the global thought, modernity, science and the different schools of thought in which the past is strongly reflected in the present. This situation necessitates redefining, deconstructing and criticizing the past in order to re-understand and digest it rational by the appropriate and accurate method of scientific view. This is carried out with the guidance of the new epistemic foundations which could reshape the role of the past in our lives, and stop the persistent questions about any epistemological or historical values Yet, the majority of Arab thinkers, pioneered by Arkoun, who are concerned with contemporary Arab thought, believe that the road map to possess a rational and non-rational modernity requires starting with the completion of the precondition related to globalization, that pushes on reality: epistemologically, ideologically, interpretively, religiously and historically on the different levels of calling, reading, deconstructing, criticizing, and interpreting the heritage. In this paper I tackled Arkoun’s vision towards the problems imposed by globalization.